Forms of Agency Constructed and Represented among Afghan Women in Deborah Rodriguez’s The Little Coffee Shop of Kabul from a Spivakian Postcolonial Feminist Perspective - Ambreen Hanif; Dr. Irfan Ali Shah; Eman Shad (Policy Journal of Social Science Review, 2026)
The representation of Afghan women in Western literature has often depicted as silent, week, oppressed, and passive, frequently overlooking their courage, resistance, and agency. This study examines the forms of agency constructed among Afghan women in Deborah Rodriguez’s novel The Little Coffee Shop of Kabul (2011). Drawing on Gayatri Chakravorty Spivak’s concepts of subalternity, epistemic violence, and strategic essentialism, the study examines how female characters negotiate socio-political, and socio-cultural constraints. The study employs a close textual analysis grounded in Catherine Belsey’s theoretical framework. The findings reveal that Afghan women exercise agency through solidarity, mutual support, resilience, self-determination, and identity formation. This suggest that agency is not limited to open resistance but often emerges through everyday actions and personal choices. Keywords: Afghan women’s agency, postcolonial feminism, Spivak’s subalternity, strategic essentialism, Western representation